Carboxylated superparamagnetic Fe3O4 nanoparticles modified with 3-amino propanol and their application in magnetic resonance tumor imaging - Changyuan Wang; Yang Wang; Wangchuan Xiao; Xiaohua Chen; Renfu Li; Zhiyong Shen; Fengchun Lu (BMC Cancer, 2023)
Abstract Background Ultrasmall superparamagnetic iron oxide (USPIO) nanoparticles are of potential magnetic resonance imaging (MRI) contrast agents for tumor diagnosis. However, ultrasmall particle size or negative surface charge lead to relative short half-life which limit the utilization of USPIO for in vivo MRI contrast agents. Methods Superparamagnetic Fe3O4 nanoparticles coated with polyacrylic acid (PAA)were synthetized, and modified by 3-amino propanol and 3-diethyl amino propyl amine. The characteristics of superparamagnetic Fe3O4 nanoparticles were investigated through transmission electron microscopy, X-ray diffraction analysis, Zata potential analysis, thermogravimetric analysis, and relaxation properties analysis. Magnetic resonance imaging animal experiment was performed. Results The synthetized nanoparticles were irregular spherical, with small particle size, few agglomeration, and good dispersion in water. After modification, the potential fluctuation of nanoparticles was small, and the isoelectric point of nanoparticles changed to high pH. After 3-amino propanol modification, the weight loss of the curve from 820 to 940 °C was attributed to the decomposition of 3-amino propanol molecules on the surface. The T1 relaxation rate of nanoparticles changed little before and after modification, which proved that the modification didn’t change the relaxation time. Brighter vascular images were observed after 3-amino propanol modification through measurement of magnetic resonance tumor imaging. Conclusion These data indicated the Fe3O4 nanoparticles modified by 3-amino propanol should be a better contrast agent in the field of magnetic resonance tumor imaging.